Predicting Counterproductive Performance Among Temporary Workers: A Note - POSTHUMA, RICHARD A.; CAMPION, MICHAEL A.; VARGAS, AMBER L. (Industrial relations (Berkeley), 2005)
Using prehire biographic and work history data, temporary help agency workers (N= 201) were classified as marginal or satisfactory. Marginal temps had characteristics suggesting poor work histories and willingness to accept any kind of employment. In prior jobs, they were paid less and more likely to have been laid off. They had also been temps for longer periods of time, and were more willing to work weekends and nights. The classification of temps as marginal versus satisfactory was validated using posthire data, showing that marginal temps had lower performance evaluations, and exhibited more counterproductive behaviors (e.g., late, absent, unsafe, or careless).